Pengaruh Literasi Keuangan dan Sikap Keuangan Terhadap Pengelolaan Keuangan Ibu Rumah Tangga Dengan Self Efficacy Sebagai Variabel Intermediasi - Rahmatika, Arivatu Ni’matu; Widyaningsih, Bekti; Al Qaedah, Alifiyah (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2024)
Abstract The objective of this research is to examine how financial literacy and financial attitudes impact the management of household finances, with self-efficacy serving as a mediating factor. Using a quantitative approach and SmartPLS4 analysis, data were collected through questionnaires from 70 housewives who are students of the Islamic economics study program. The results show that financial literacy has a significant impact on household financial management and also significantly affects self-efficacy. Self-efficacy was also found to significantly influence household financial management. However, financial attitudes do not show a significant impact on household financial management, although they do have a significant effect on self-efficacy.